/x/-\(\dfrac{3}{4}=\dfrac{5}{3}\)
\(\Leftrightarrow\) /x/ = \(\dfrac{5}{3}+\dfrac{3}{4}\)
\(\Leftrightarrow\) /x/ = \(\dfrac{29}{12}\)
TH1: x =\(\dfrac{29}{12}\)
TH2: x = -\(\dfrac{29}{12}\)
Vậy x = \(\dfrac{29}{12}hoặc\) x = -\(\dfrac{29}{12}\)
\(\left|x\right|-\dfrac{3}{4}=\dfrac{5}{3}\)
\(\Leftrightarrow\)\(\left|x\right|=\dfrac{5}{3}+\dfrac{3}{4}\)
\(\Leftrightarrow\)\(\left|x\right|=\dfrac{29}{12}\)
\(\Leftrightarrow\)\(\left[{}\begin{matrix}x=\dfrac{29}{12}\\x=\dfrac{-29}{12}\end{matrix}\right.\)
Vậy x=\(\dfrac{29}{12}\) hoặc x=\(\dfrac{-29}{12}\)
Chúc bạn học tốt !